Designing The Concepts of “The Maturity Level of Netizen”: How To Manage Comment & Critics Profiling 1.0 - Sasono Wibowo; Indra Gamayanto; Dewi Agustini Santoso (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Social media is a new life influenced by the development of information technology. This development raises problems in comments and criticism on social media and the rapid growth of hoax information that affects many sectors of life. This article is the development of two journals: The Development and Implementation of Wise Netizens (E-Commentary) In Indonesia & Social Media and Changing Communication Patterns. The method used is the Johari window, and this method is developed and combined with the concept of comments and criticism on social media. The result of this article is a formula N=K.C2, a unique formula made for netizens and the seven stages of wise netizens (The maturity level of netizens). Furthermore, this formula and framework will provide netizens with a solution to assess them. To what extent a netizen has become wise in making comments and criticisms on social media? Furthermore, these stages will be used to find out, analyze and assess the extent to which comments and critics made by netizens have reached a level that has a standard of communication quality, share their knowledge, and have a two-way discussion.